Enzymatic production of trans‐4‐hydroxy‐l‐proline by proline 4‐hydroxylase. Issue 2 (3rd July 2020) - Chen, Xiulai; Yi, Juyang; Liu, Jia; Luo, Qiuling; Liu, Liming
Summary: Trans ‐4‐hydroxy‐l ‐proline (Hyp) is a useful chiral building block for production of many nutritional supplements and pharmaceuticals. However, it is still challenging for industrial production of Hyp due to heavy environmental pollution and low production efficiency. To establish a green and efficient process for Hyp production, the proline 4‐hydroxylase ( Ds P4H) from Dactylosporangium sp. RH1 was overexpressed and functionally characterized in Escherichia coli BL21(DE3). The recombinant Ds P4H with l ‐proline as a substrate exhibited K m, k cat and k cat / K m values up to 0.80 mM, 0.52 s −1 and 0.65 s −1 ·mM −1 respectively. Furthermore, Ds P4H showed the highest activity at 35°C and pH 6.5 towards l ‐proline. The highest enzyme activity of 175.6 U mg −1 was achieved by optimizing culture parameters. Under the optimal transformation conditions in a 5‐l fermenter, Hyp titre, conversion rate and productivity were up to 99.9 g l −1, 99.9% and 2.77 g l −1 h −1 respectively. This strategy described here provides an efficient method for production of Hyp and thus has a great potential in industrial application. Abstract : Trans ‐4‐hydroxy‐l ‐proline (Hyp) is a useful chiral building block for production of many nutritional supplements and pharmaceuticals. Here, the proline 4‐hydroxylase (DsP4H) from Dactylosporangium sp. RH1 was overexpressed and functionally characterised in Escherichia coli BL21(DE3) to improve enzymatic production of Hyp. Under the optimal transformation conditions in a 5‐l fermenter, Hyp titer, conversion rate, and productivity were up to 99.9 g l −1, 99.9%, and 2.77 g l −1 h −1, respectively.